2003
DOI: 10.1002/joc.958
|View full text |Cite
|
Sign up to set email alerts
|

The teleconnections between the extreme phases of the southern oscillation and precipitation patterns over Turkey

Abstract: Climatic links between monthly precipitation in Turkey and the El Niño and La Niña events using the empirical methodology of Ropelewski and Halpert are investigated. Coherent and significant precipitation responses to both the extreme phases of the southern oscillation (SO) are found in two core regions, namely western Anatolia (WA) and eastern Anatolia (EA). The geographical extent of the two regions, together with a defined signal season for each tropical event, are identified. For WA, the April-July wet per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…long‐term periods in the SOI), the anti‐phase was detected at most of the stations. As can be seen in the results of this research, the SOI has stronger effects on precipitation in Iran, similar to the results obtained in neighbouring countries such as India, Nepal and Turkey (Mooley et al , ; Shrestha, ; Çag̀atay Karabörk and Kahya, , ). It seems that the climatic indices which are derived from sea surface temperature, such as the SOI, have more noticeable influences on the precipitation in this region compared to the climatic indices which are based on pressure systems, such as NAO, and this result is in agreement with previous studies in neighbouring regions (Çag̀atay Karabörk and Kahya, , ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…long‐term periods in the SOI), the anti‐phase was detected at most of the stations. As can be seen in the results of this research, the SOI has stronger effects on precipitation in Iran, similar to the results obtained in neighbouring countries such as India, Nepal and Turkey (Mooley et al , ; Shrestha, ; Çag̀atay Karabörk and Kahya, , ). It seems that the climatic indices which are derived from sea surface temperature, such as the SOI, have more noticeable influences on the precipitation in this region compared to the climatic indices which are based on pressure systems, such as NAO, and this result is in agreement with previous studies in neighbouring regions (Çag̀atay Karabörk and Kahya, , ).…”
Section: Resultssupporting
confidence: 91%
“…A study in Nepal showed that the influences of the SOI are very significant for Nepal's monsoon, since when the SOI is in a negative (positive) phase, rainfall is lower (higher) than the normal values (Shrestha, ). As seen in previous studies in Turkey, the SOI phases play major roles in the Turkish and the eastern Mediterranean regions' precipitation, even when the SOI is in the extreme phase (Çag̀atay Karabörk and Kahya, , ). It seems that the SOI plays a major role in the precipitation amount and occurrence in this region, and the previous studies agree with the main results of this research.…”
Section: Resultssupporting
confidence: 57%
“…[18] An empirical methodology similar to that adopted by Ropelewski and Halpert [1986, 1987, 1996, Piechota and Dracup [1996] and Karabörk and Kahya [2003] was used to determine the impact of El Niño and La Niña years on global drought conditions. The approach followed that of a previous study [Vicente-Serrano, 2005] that analyzed the impact of ENSO events on droughts in the Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…Where they exist, relationships between ENSO and the climate indices are generally stronger for temperature indices than for the precipitation in the region (Donat et al, 2014). However, variation in precipitation (Karabork and Kahya, 2003) and streamflow in parts of Turkey is affected by ENSO (Kahya and Karabörk, 2001) but the signal is mixed and differs between northwest and eastern Turkey. Work to date indicates that there are no obvious effects of EP El Niño in terms of surface air temperature anomalies, but CP El Niños are associated with a positive temperature anomaly in southeast Iraq and Saudi Arabia (Graf and Zanchettin, 2012).…”
Section: Western Asiamentioning
confidence: 99%